The mystery in Venice - Stilton, Geronimo. (Scholastic, 2012)
Accepting an ugly crystal figurine from Petunia Pretty Paws, Geronimo Stilton discovers a mysterious message inside the figurine from a Venetian mouse who requires assistance.